Clinical utility of a newly developed microfluidic device for detecting circulating tumor cells in the blood of patients with pancreatico‐biliary malignancies. (6th November 2020) - Konno, Naoki; Suzuki, Rei; Takagi, Tadayuki; Sugimoto, Mitsuru; Asama, Hiroyuki; Sato, Yuki; Irie, Hiroki; Hikichi, Takuto; Ohira, Hiromasa
Abstract: Background: The development of an optimal screening method is required to improve the prognosis of pancreatico‐biliary (PB) cancers. A recently developed microfluidic device achieved a high diagnostic yield by detecting circulating tumor cells (CTCs) in the blood of cancer patients. We conducted this study to investigate the clinical utility of measuring CTCs in peripheral venous blood to diagnose PB cancer. Methods: Sixty‐three subjects were enrolled in this study (29 with pancreatic cancer [PC], 19 with biliary cancer [BC] and 16 non‐tumor controls). Using a microfluidic chip device and image analyzer, circulating blood cells were selected based on their size and immunocytochemistry staining pattern. The primary endpoint was the diagnostic accuracy of CTCs with regard to distinguishing between PB cancer patients and controls. We divided all cases into the training set (n = 32) and validation set (n = 31). The diagnostic accuracy of CTCs, carcinoembryonic antigen (CEA) and cancer antigen 19‐9 (CA19‐9) were analyzed. Results: In both the training set and validation set, CTCs showed the highest diagnostic accuracy (training set: CTCs 90.6%, CA19‐9 90.6%, CEA 65.6%, validation set: CTCs 87.5%, CA19‐9 78.1%, CEA 81.2). Regarding non‐metastatic PC (cStage I‐III, n = 11), CTCs also had the highest diagnostic accuracy among the three markers tested (CTCs: 84.6%, CA19‐9:80.7%, CEA 73.0%). Conclusions: A newly developed microfluidic device could diagnose PB cancers by detecting CTCs. This trial was registered with the UMIN Clinical Trials Registry, no. UMIN000029808. Abstract : Highlight In this prospective study, Konno and colleagues investigated the clinical utility of a newly developed microfluidic chip device for detecting circulating tumor cells in the blood of patients with pancreatico‐biliary malignancies. They concluded that circulating tumor cells could be a more accurate diagnostic and prognostic marker than CEA and CA19‐9.